Pertanggungjawaban Pidana Pelaku Pengeroyokan Yang Menyebabkan Luka Tumpul: (Studi Putusan Nomor 576/Pid.B/2021/PN.Tjk) - Zainab Ompu Jainah; Intan Nurina Seftiniara; Muhammad Yudha Novandre (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
Crimes committed by a criminal will have a risk that must be borne by a criminal, this risk may result in the perpetrator of the crime having to account for his actions in the form of confinement which of course is based on the provisions stated in positive Indonesian law, namely according to what is stated in the law. In the Criminal Code, accountability is one of the forms of crime that must be accounted for by the perpetrator of the crime, in committing the crime it is known that there are several factors that cause the perpetrator to commit a crime, the result of a crime committed by the perpetrator has an impact on the victim, resulting in the victim the condition of his health became bad, due to the persecution in the form of beatings by the perpetrators.